As fundadoras do Instituto de Matemática e Física da Universidade da Bahia On the founders of the Institute of Mathematics and Physics, University of Bahia - André Luís Mattedi Dias (História, Ciências, Saúde: Manguinhos)
É surpreendente a presença de mulheres no corpo discente do curso de matemática da Faculdade de Filosofia da Universidade da Bahia (FF/UFBA). Ainda hoje elas concentram-se em áreas tradicionalmente tidas como femininas e os homens predominam nas áreas matemáticas. Examinei depoimentos de algumas mulheres que cursaram matemática e que depois tornaram-se professoras da FF. Para elas, a matemática não significou apenas uma opção pelo magistério no ensino médio. Tornaram-se a maioria do corpo docente de matemática da FF e do Instituto de Matemática e Física (IMF), fundado em 1960. Sigo a trajetória delas, inicialmente como estudantes, depois como assistentes e professoras, e finalmente como fundadoras do IMF. Destaque especial para Martha Maria de Souza Dantas, organizadora do I Congresso Brasileiro de Ensino da matemática, evento que desencadeou o processo de fundação do IMF; e para Arlete Cerqueira Lima, articuladora do processo que resultou na fundação do IMF. The reduced number of female students of mathematics at the University of Bahia School of Philosophy (Faculdade de Filosofia, Universidade da Bahia - FF/UBa) is quite surprising. To date, they are concentrated in areas traditionally viewed as feminine whereas men predominate in the mathematical fields. I have examined interview data from a few women who graduated in mathematics and went on to teach at the University of Bahia School of Mathematics (Faculdade de Filosofia - FF) and at the Institute of Mathematics and Physics (Instituto de Matemática e Física - IMF), where they were soon to outnumber men and constitute the majority of the mathematics teaching staff. In this study, I have investigated the course of their careers over time: from their early student days, through their time as teaching assistants and professors, and finally as founders of the Institute of Mathematics and Physics, in 1960. Special reference is made to Martha Maria de Souza Dantas, organizer of the I Brazilian Conference on Mathematics Teaching, an event which has provided the groundwork for what was to become the Institute (IMF); and to Arlete Cerqueira Lima, the mastermind behind its creation.